Vivir y morir según la ley. Reflexiones teóricas interdisciplinarias sobre la vida de la persona y el derecho a la vida - Siverino Bavio, Paula (2012)
To live and die according to law. Interdisciplinary theoretical thoughts on person’s life and the right to life The article discusses different considerations on the right to lifeand life protected by law from an anthropologic and legal bioethics perspective based on the analysis made between «the living’s life» and «the person’s life» distinctions as well as thoughts about ill person’s will restrictions at the final stage of his life.